GENERATIONAL DIFFERENCES TOWARD ORGANIC FOOD BEHAVIOR - Burcu Erdal; Sule Turhan; Pinar AYdin Temel (Journal of Animal and Plant Sciences, 2023)
The aim of this paper is to identify factors influencing the purchase intention of generations towards organic products in Bursa, Türkiye. The study was conducted with a quantitative approach with data collection from 395 respondents in Bursa City between November 2023 and February 2022. The results were investigated using descriptive analysis, reliability analysis, exploratory factor analysis, correlation analysis, chi-square analysis and regression analysis. It is important to consider generational characteristics in order to achieve realistic results in organic product consumption studies. Thus, marketers will be provided with a different perspective and they will develop more consistent marketing strategies. In this research, it has been determined that the reasons for buying a product differ in the context of generations. According to the results, especially the consumers in the Y Generation are more interested in the concept of organic products. It is seen that social media is the most effective (43%) source of organic product information. According to the results of the factor analysis, the environmental friendliness of organic products and the high nutritional value of organic products are the first preferences of consumers. The least important variable is the reliability of organic products. Within the scope of the research, the organic food product trends of 5 generations were discussed. According to the results obtained, it has been determined that the tendency of the Z Generation towards organic food is lower than that of the X and Y Generations. It can be thought that this situation is due to the fact that they are young and do not have enough economic power yet. It is clearly seen that generational characteristics affect the consumption of organic products. This result will help to identify the problems and opportunities in the organic product market. Raising awareness, informing and directing individuals towards organic products in a way that covers all generations will be an important step in terms of both the country’s economy and the healthy functioning of the ecosystem.
Keywords: Organic; generations; consumption; organic fodd; organıc farming; Turkey